2024
DOI: 10.1002/adfm.202403490
|View full text |Cite
|
Sign up to set email alerts
|

A Room‐Temperature Curing Plant Protein‐Based Adhesive with High Strength and Flame Retardancy for Heat‐Free Adhesion

Ke Jiang,
Xuemei Dong,
Yuan Chen
et al.

Abstract: Plant protein‐based adhesives are gaining traction owing to their low cost and eco‐friendliness. However, achieving flame retardancy and long‐term water resistance in them under room‐temperature curing conditions remains a challenge due to the hydrophilicity and low reactivity of plant proteins. Herein, a novel adhesive synthesized from soybean meal (SM), activated sodium alginate (aSA), nano‐hydroxyapatite (nHA), and polyamidoamine‐epichlorohydrin (PAE) resin addresses this challenge. aSA as a reactive bio‐ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Figure h showcases the surface crack conditions of the SM-based adhesives, which assessed their toughness. While large cracks developed on the SM adhesive, the SM/Ker/0.4%La@SA and SM/Ker/0.8%La@TSA adhesives exhibited dense and smooth surfaces without cracks or holes, indicating improved toughness . The force–distance curves and work of adhesion revealed that the work of adhesion of the SM/Ker/0.4%La@SA adhesive increased to 0.60 J, a 71.4% increase compared with the SM adhesive (0.35 J) (Figure i).…”
Section: Resultsmentioning
confidence: 99%
“…Figure h showcases the surface crack conditions of the SM-based adhesives, which assessed their toughness. While large cracks developed on the SM adhesive, the SM/Ker/0.4%La@SA and SM/Ker/0.8%La@TSA adhesives exhibited dense and smooth surfaces without cracks or holes, indicating improved toughness . The force–distance curves and work of adhesion revealed that the work of adhesion of the SM/Ker/0.4%La@SA adhesive increased to 0.60 J, a 71.4% increase compared with the SM adhesive (0.35 J) (Figure i).…”
Section: Resultsmentioning
confidence: 99%